ผลงานและแนวการกำกับภาพยนตร์ของวิจิตร คุณาวุฒิ - พาขวัญ ชินพัฒนวานิช (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
This research, based on the autuer theory, aims to study the background, the experiences, the movies and film directing in order to find out the directing styles of Vichit Kunavudhi. This is done by studying the movies he made and by depth interview of relevant key informants. It is found that the main background and identity of Vichit Kunavudhi are his ability in writing and his direct experiences. Besides, his systematic approaches in the way he thinks and the way he works, together with his sensitivity and imagination, his love of nature, and his inquisitive mind collectively influence his directing styles and his movies. Vichit controls all important components of his production : writing the screenplay, directing and editing, while leaving the management to other people. This is the sure way of controlling every step of story telling in order to maintain the message and the quality of communication in the fashion of story-teller. These findings conform with the auteur theory which says that the film director is virtually the author of the film. Vichit’s style of film directing is a combination of many patterns and concepts. However, his focus remains on realistic and natural appearances of various components, the emotional expression in acting, and the overall atmosphere of the movies. Moreover, the themes that usually reappear in his movies involve human dignity, concepts in Buddhism and his own interest as a naturalist.